Clinical characterization of 52 patients with immunoglobulin G4-related disease in a single tertiary center in Japan: Special reference to lung disease in thoracic high-resolution computed tomography. (November 2017) - Saraya, Takeshi; Ohkuma, Kosuke; Fujiwara, Masachika; Miyaoka, Chika; Wada, Shoko; Watanabe, Takayasu; Mikura, Sunao; Inoue, Manami; Oda, Miku; Sada, Mitsuru; Ogawa, Yukari; Honda, Kojiro; et al.
Abstract: Background: Immunoglobulin G4-related disease (IgG4-RD) is a rare multi-organ disorder. Physicians rarely encounter patients with IgG4-RD and its range of symptoms. Methods: To elucidate the clinical characterization of IgG4-RD, along with the clinical significance of lung involvement, we retrospectively reviewed the medical records of patients who satisfied the comprehensive diagnostic criteria for IgG4-RD. Results: We identified 52 patients with IgG4-RD. Of these, 32 patients underwent tissue biopsies, resulting in categorization as definite (n = 23) or possible (n = 9) IgG4-RD cases. Among the 23 definite IgG4-RD cases, those with positive lung involvement (n = 8) had significantly higher values of serum LDH (median 220 IU/L, interquartile range (IQR) 175–378 vs. median 184, IQR 136–249, p = 0.039), IgG (median 2769 mg/dL, IQR 2028–7807 vs. median 2048, IQR 1168–4376, p = 0.009), and soluble interleukin-2 receptors (median 1620 U/mL, IQR 871–2250 vs. median 733, IQR 271–1600, p = 0.003) than those with negative lung involvement (n = 15). Similarly, a significant number of patients with positive lung involvement were positive for rheumatoid factor (71.4% vs. 23.1%, p = 0.041) or hypocomplementemia (50% vs. 0%, p = 0.036). Sixteen patients also showed lung involvement (definite n = 8, possible n = 8); thoracic computed tomography (CT) of these patients revealed mediastinal lymphadenopathies (n = 14, 87.5%), ground glass opacity (n = 11, 68.8%), consolidation (n = 8, 50%), thickening of the bronchovascular bundles (n = 7, 43.8%), small nodules (n = 5, 31.3%), bronchiectasis (n = 4, 25%), and reticular shadows (n = 4, 25%), and pulmonary function tests, using a standard technique involving a single breath, revealed decreased diffusion capacity for carbon monoxide. Conclusions: IgG4-RD is associated with diverse thoracic CT findings and a decreased diffusion capacity, and careful multidisciplinary assessment is needed to enable differentiation of IgG4-RD from lymphoproliferative disorders. Highlights: Serum levels of LDH, IgG, and soluble IL-2R are significantly higher in positive lung involvement than in negative patients. The lung involvement in IgG4-related disease might be linked to a more intense inflammatory reaction. The lung involvement patients have high occurrences of positive RF or hypocomplementemia. IgG4-RD is associated with diverse thoracic CT findings and a decreased diffusion capacity. Decreased diffusion capacity might reflect the activation of lymphocytes and/or plasma cells that accumulate in interstitium.